Rain induced attenuation studies for v-band frequency in tropical regions - Badron, Khairayu; Ismail, Ahmad Fadzil; Din, Jafri; Abdul Rahman, Tharek (2009)
Satellite links operating at frequencies above 10GHz in the tropics typically suffer severe signal degradation due to rain. The study attempts to investigate the impacts of rain on the performance of satellite-Earth links at V-band frequency. Attenuation due to rain at 38GHz had been measured for a period of 20 months in Malaysia. Studies are being conducted to quantify the rain-induced degradations. Preliminary analyses include seasonal variations and the annual cumulative distributions. Obtained results are compared with several prediction models including the ITU-R.